Transnational connections and the Arab Gulf - Al-Rasheed, Madawi (London ; New York : Routledge, 2005)
This book challenges the definitions of globalisation and transnationalism as a one way process generated mainly by the Western World and the view that the latter is a twentieth century phenomenon.
An anational society : eastern Arabia in the Ottoman period / Frederick Anscombe -- Mapping the transnational community : Persians and the space of the city in Bahrain, 1869-1937 / Nelida Fuccaro -- Transnational merchants in the nineteenth-century Gulf : the case of the Safar family / James Onley -- Dubai : global city and transnational hub / Roland Marchal -- The emergence of a pan-Arab market in modern media industries / Gaëlle le Pottier -- Indonesians in Saudi Arabia : religious and economic connections / Mathias Diederich -- Saudi religious transnationalism in London / Madawi Al-Rasheed -- Wahhabism in the United Kingdom : manifestations and reactions / Jonathan Birt.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Persian Gulf States -- Civilization; Persian Gulf Region -- Civilization; Political culture -- Persian Gulf States; Political culture -- Persian Gulf Region; Group identity -- Persian Gulf States; Group identity -- Persian Gulf Region; Space and time -- Sociological aspects; Identité collective -- États du golfe Persique; Identité collective -- Persique, Région du golfe; États du golfe Persique -- Civilisation; HISTORY -- General; Group identity -- Persian Gulf States; Group identity -- Persian Gulf Region; Space and time -- Sociological aspects; Political culture -- Persian Gulf States; Political culture -- Persian Gulf Region; Persian Gulf States -- Civilization; Persian Gulf Region -- Civilization; Civilization; Group identity; Political culture; Space and time -- Sociological aspects; Persian Gulf Region; Persian Gulf States